Pembelajaran Bahasa Arab Dengan Menggunakan Media Audio, Visual, dan Audiovisiual di MTsN 1 Kota Makassar - Arsal, Fathur Riyadhi; Hermawan, Acep; Kosim, Nanang (Universitas KH. Mukhtar Syafaat, 2024)
Good learning media must be used to support learning. In general, there are three types of learning media, namely audio media, visual media, and audiovisual media. This research wants to know how audio, visual, and audiovisual media are applied at MTsN 1 Makassar City so that learning is not monotonous for students. This research uses qualitative and descriptive methodology. The data collected for this study came from Arabic language learning at MTsN 1 Makassar City. The data sources in this study consisted of G1, G2, and G3 who were Arabic language teachers at MTsN 1 Makassar City. Data collection techniques in this study were interviews and observations. The results of this study found that learning using audio media alone is very rarely used, but in some times they simply apply it by reading the text directly to students, then Arabic language learning using visual media at MTsN 1 Makassar City is quite often rather than audio media. This is because visual media is more helpful for teachers in visualizing their explanations, then the use of audiovisual media is sometimes only on a few occasions or. In the use of auidiovisual media, teachers often provide spectacles such as movies, cartoons, or video clips related to learning.